Transformative Adult Learning Strategies: Assessing the Impact on Pre-Service Administrators' Beliefs - Kathleen M. Brown (Educational Considerations, 2005)
The purpose of this article is to explore the effects of an alternative, transformative andragogy, i.e., the art and science of helping others to learn, designed to be responsive to the challenges of preparing educational leaders committed to social justice and equity.